CALCULATION OF TECHNOLOGICAL PARAMETERS OF OUT-PIPE REAGENT CIRCULAR IRRIGATION OF GRAVEL-PACKED FILTERS OF WATER SUPPLY WELLS - V. V. Ivashechkin; V. V. Veremenyuk; P. A. Avtushko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The purpose of this work is the study of decolmatation rate of granular layer of gravel pack of well during creating inside of it flushing of reagent with given hydrodynamic parameters and determination the duration of treatment. This article deals with radical movement of chemical solutions by injection of it outside of gravel pack of filter when the flow directs to borehole axis under conditions of quasi-steady-state mode of filtration for equal yield of input and output reagent from borehole.Colmataged layer of gravel pack is schematized in the form of porous ring cylinder with outside radius which is equal to radius of line of gravel pack and the height which is equal to the length of filter made in formation drilling and inside radius which is equal to radius of filter. Initial saturation of subsoil with colmatant is given. It was accepted that reagent with given rate flows through outside surface of ring cylinder equal along all height. Near-filtering zone is given uniform and movement is quasi-steady-state.Equations’ system is composed including: joint equation of movement and mass conservation and generalized equation of kinetics, which describes kinetics of colmatant dissolution in the regime of out-pipe watering of ring gravel pack of well taking into account the change of structure of porous medium. The analytic solution of equations’ system was obtained, which allow to calculate salt content in reagent during the leaching process and to determine the specific volume of deposits in the point of gravel pack at any moment of time in the process of regent injection. The analytic dependence was obtained for calculation of duration of complete regeneration of soil grains’ layer of outer contour of gravel packing. For calculation of duration of full regeneration of the whole thickness of packing it is suggested to divide the regeneration period into a series of stages of salt transferring from subsoil. Duration of one stage is equal to time which is necessary for reagent to pass ring part. Each phase is calculated  separately, as the initial specific volume of deposits in inflow section is changing after each previous phase, and this demands the correction of border conditions. Methods of stage calculation of regeneration duration for achievement of required level of decolmatation is realized on computer